PENGARUH MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA PEGAWAI PADA KANTOR MIS. AL KHAERAT DESA TADA KECAMATAN TINOMBO KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Hikmah Hikmah (AkMen JURNAL ILMIAH, 2015)
Humans have an important role in every activity / work in an organization or institution because humans become planners, perpetrators and decisive realization of the organization / institution. The goal is not possible without the active role of its employees even though the tools owned by an agency so sophisticated. The location of this research on MIS office. Al Khaerat Village District of Tinombo Tada Moutong Parigi district, Central Sulawesi is located at Jl. Trans Sulawesi. Populasi in this study were all employees at MIS office. Al Khaerat Village District of Tinombo Tada Moutong Parigi district, Central Sulawesi 38 people. Samples are some of the studied population or number of sections that represent for examination. Given a population of less than 100 people, the sample is drawn is that 38 people overall sample. Calculation results obtained determination coefficient of 0.871 when converted into percentage is 87.10 per cent in this case used Adjusted R Square (corrected value) as the independent variable three variables then the value of 0.867 if dikonfersi into percentage figures are obtained 86.70 percent and indicated the amount is quite high and means that the amount of 86.70 percent jointly independent variable can explain the variation of the dependent variable.